Steric effects on molecular adsorption at columnar surfaces : A model for the adsorption of pyridine on gold electrodes - Gómez, M. M. (1999)
Results for pyridine (Py) adsorption on columnar-structured (cs) gold substrates from acid solutions at different potentials and 298 K are compared to the predictions of a recently proposed Langmuirian adsorption model at columnar surfaces. The difference in the apparent adsorption Gibbs energy derived from the adsorption isotherm of Py on cs- and smooth gold substrates was accounted for by a correction factor (f) that depends on the roughness (R) of the substrate according to f∝R−n, as expected from Monte Carlo simulation of the model. This agreement indicates that the substrate geometry plays a key role in the interpretation of adsorption isotherms.